Perancangan alat penukar panas APK berbahan bakar sekam padi untuk pengering udang rebon kapasitas 50 Kg - Mulyana, Mulyana; Rahardiansyah, Raeksy; Oleh, Oleh; Santosa, Aa (Universitas Muhammadiyah Metro, 2024)
50 kg wet rebon shrimp drying machine is an energy-saving tool that works by flowing hot air with a temperature between 40 to 50 degrees Celsius to the surface of rebon shrimp. The main component of this drying machine is heat exchanger. Air and husks are burned to produce heat energy. The gas then passes through the heat exchanger tube using a heat exchanger. The heat exchanger used is a cross-flow heat exchanger, meaning that the gas released after burning the husk is not mixed with the air fluid. To determine the performance of the heat exchanger, the construction plan is designed using the IMTD approach and as effective as possible because CFD simulation is integrated into Anys15.0. The results of previous measurements and calculations are the input data entered into the application. With a turnaround time of 8 hours, 50 kg of fresh rebon shrimp can be dried to 31.2 kg of water thanks to the 103.5 watt heat flow rate from the air dryer.